Galeatylinae, a new subfamily of Atylidae for Galeatylus coripes, new genus and species, from the Bass Strait, south-eastern Australia (Amphipoda, Dexaminoidea) - Just, Jean (Zootaxa, 2019)
Galeatylinae, a new subfamily in the Atylidae, for Galeatylus coripes new genus and species, is reported from the Bass Strait in the south-east of Australia. This is the first record of the Atylidae from Australia.